Autoimage as a Predictor of Academic Performance: Case of adult literacy - Muller Ferres, Pablo; Vera Gajardo, Nathaly (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2017)
This is article linking two concepts which although fundamentals in the development of formal education, rarely studied together. The self-image or self-concept, of the student and the teacher's role in the classroom. We intend to link these concepts to answer if a teacher that encourages his students to create a good concept of them generates better learning than one without; for that we worked with adult literacy teachers, to whom will be surveyed in relation to 13 variables previously determined by a semantic network. The results show that teachers who validate selfimage in their students achieve a shorter training slope than that achieved literacy not working on this concept.